PRAKTIK EKSEKUSI RIIL TANAH MILIK MASYARAKAT ADAT SUNDA WIWITAN - Hazar Kusmayanti; Sandi Yusta Hawari (SASI, 2020)
At the time of the riil execution, it was not uncommon to encounter obstacles which caused the execution to not be carried out. One of them is the case of the Supreme Court Decision Number 2394 K/Pdt/2010. Therefore the researcher wants to examine the things that cause riil execution cannot be carried out in terms of civil procedural law and what legal actions can be carried out by the applicant for execution due to riil execution that cannot be carried out in connection with a civil law. The research method used is a normative juridical,analytical methods used in the data are qualitative normative. Based on the research, it can be concluded that what caused the riil execution of the Supreme Court's Decision Number 2394 K/PDT/2010 on 12 January 2012 could not be implemented because of the resistance carried out by the parties executed and third parties carried out by the Sunda Wiwitan indigenous people by carrying out physical resistance which caused casualties to the execution, resistance efforts are carried out to obstruct the process of execution and Legal actions that can be carried out by the applicant for execution due to riil execution that cannot be carried out that is by way of the applicant's execution can submit a request for execution again to the Chairperson of the Kuningan District Court to carry out the second execution.